Hsp90α promotes lipogenesis by stabilizing FASN and promoting FASN transcription via LXRα in hepatocellular carcinoma - Zihao Deng; Lixia Liu; Guantai Xie; Zhenming Zheng; Jieyou Li; Wenchong Tan; Yaotang Deng; Jinxin Zhang; Manfeng Liang; Yingxia Wu; Zhifeng Zhou; Yan Li; et al. (Journal of Lipid Research)
Excessive lipid accumulation promotes the occurrence and progression of hepatocellular carcinoma (HCC), accompanied by high levels of fatty acid synthetase (FASN) and more active lipogenesis. Heat shock protein 90 (Hsp90) acts as a chaperone to maintain the stability and activity of the client proteins. Studies have revealed that Hsp90 regulates the lipid metabolism of HCC, but the effect of Hsp90 on FASN still remains unknown. This study aims to discover the mechanism of Hsp90 inhibition on lipid accumulation and investigate the different effects of Hsp90 N-terminal domain inhibitor STA9090 and C-terminal domain inhibitor novobiocin on FASN protein stability and transcription pathway in HCC. We found that HCC cells tended to store lipids, which could be disrupted by Hsp90 inhibitors in vivo and in vitro. High levels of Hsp90α and FASN in tumor tissue had correlation with poor prognosis of HCC patients, and Hsp90α interacted with FASN to maintain its protein stability. Furthermore, N-terminal domain of Hsp90α was essential for process of sterol regulatory element binding protein 1 to activate FASN transcription and Hsp90α prevented proteasomal degradation of liver X receptor α to upregulate FASN transcription via liver X receptor α/sterol regulatory element binding protein 1 axis. Our data reveal that Hsp90α promotes lipid accumulation by increasing the protein stability and FASN mRNA transcription, and can be alleviated by Hsp90 inhibitors, which provides a theoretical basis for Hsp90-targeted therapy on lipid metabolism in HCC.